The dynamics of communication manager - medical team - patient - Honcea , Adina; Stoicescu , Ramona Mihaela; Bratu, Iulian; Schroder, Verginica; Coteș , Adriana Florina; Adumitresi, Cecilia; Dumitru , Virginia (Technium BioChemMed, 2023)
„To communicate” is in general considered as verbal or nonverbal behaviour in a social context. verbal într-un context social. Communication includes all those symbols a person uses in offering or receiving an informational message. Communication is a process of offering and receiving information. Making a study about the dynamic of communication (manager- medical team- patients- caregivers) may help to analyse reliable indicators of interpersonal operation, to discover communication models of the functional or disfunctional (symptomatic) behaviour. When we communicate we learn to differentiate and let us relate through words and experiences We need to find out information obout other persons or nature of relations. We are receiving this vital information in two basic ways, verbal responses and nonverbal behaviour. People need to communicate unambigously (the message cannot be interpreteted in more ways than one) if they want to be able to give others information in a functional communication. We need to show those involved in communication what’s going on inside of us, what we expect from others, what we think we know, how we interpret what others do, what behavior we dislike or like, what are our own intentions. A person who communicates functionally can firmly support his point of view, at the same time, it clarifies and defines what was said, he is also demanding and receptive to feedback when he gets it. If you whant a functional verbal communication without assumptions and without errors both the sender and receiver have a responsability to make it so.